(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Wulandari AD, Meitiniarti VI, Kasmiyati S. 2024. Interaction between Eichornia crassipes with Microbacterium sp. SpR3 and Micrococcus luteus RT-9 in Cr6+ reduction in liquid media. Biodiversitas 25: 957-963. Water Pollution caused by Cr6+ contamination is difficult to remove from the environment. One of the efforts to reduce Cr6+ contamination in water is by bioremediation. Bioremediation using the interaction of rhizosphere bacteria with aquatic plants can be employed to decrease the content of Cr6+ in water environment. This study aimed to determine the effect of adding Microbacterium sp. SpR3, Micrococcus luteus RT-9, and a mixture of both bacteria on the ability of Eichornia crassipes to reduce the concentration of Cr6+ in the growth media and the plant’s growth potential. This study was conducted in the Microbiology Laboratory of the Faculty of Biology at Satya Wacana Christian University. Eichornia crassipes plans of similar size were grown in 450 mL of Hoaglands solution with Cr6+ 5 mg.L-1 in a container. The treatment in this study involves the addition of 50 mL (10% of the working volume) of Microbacterium sp SpR3 culture, Micrococcus luteus RT- 9, and a combination of both Cr6+-reducing bacteria. The reduction rate of Cr6+ concentration in the mixture of both types of bacteria reached 88.06%, which was higher compared to the control without the addition of the inoculum (87.08%). The inoculation of both Cr6+ reducing bacteria did not hibit the growth rate of the plants. The ability of Microbacterium sp. SpR3 and Micrococcus luteus RT-9 to reduce Cr6+ in liquid media can be employed in the bioremediation of Cr6+ contaminated wastewater.